Observation of manganese nodules and encrustations in various lakes of Finland - Halbach, Peter (Supplement to: Halbach, P (1976): Mineralogical and geochemical investigations on Finnish lake ores. Bulletin of the Geological Society of Finland, 48(1-2), 33-42, https://doi.org/10.17741/bgsf/48.1-2.004, 1975)
The limnic ferromanganese ore concretions in some Finnish lakes are described. Their chemical and mineral compositions have been measured as have their natural surroundings — the latter by means of physico-chemical in-situ analysis. The sources of the nodules' contents are discussed, and a theory based on the calculated precipitation fields of the important ore minerals is presented for the ore formation.